Factors Affecting Isoflavone Content in Soybean Seeds Grown in Thailand - Supanimit Teekachunhatean; Nutthiya Hanprasertpong; Thawatchai Teekachunhatean (International Journal of Agronomy)
Soybeans are the most common source of isoflavones in human foods. The objectives of this study were to determine the effects of Thai soybean variety, planting date, physical seed quality, storage condition, planting location, and crop year on isoflavone content, as well as to analyze the relationship between seed viability and isoflavone content in soybean seeds grown in Thailand. Isoflavone content in Thai soybeans varied considerably depending on such factors as variety, physical seed quality, crop year, planting date (even in the same crop year), and planting location. Most varieties (except for Nakhon Sawan 1 and Sukhothai 1) had significantly higher isoflavone content when planted in early rather than in late dry season. Additionally, seed viability as well as long-term storage at 10∘C or at ambient condition seemed unlikely to affect isoflavone content in Thai soybean varieties. Isoflavone content in soybean seeds grown in Thailand depends on multiple genetic and environmental factors. Some varieties (Nakhon Sawan 1 and Sukhothai 1) exhibited moderately high isoflavone content regardless of sowing date. Soybeans with decreased seed viability still retained their isoflavone content.